2017
DOI: 10.3141/2616-07
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Wrong-Way Driving Hotspots by Modeling Crash Risk and Assessing Duration of Wrong-Way Driving Events

Abstract: Because wrong-way driving (WWD) crashes are often severe, it is important for transportation agencies to identify WWD hotspot segments appropriate for potential implementation of advanced WWD countermeasures. Two approaches to identify these hotspot segments were developed and applied to a case study of limited-access highways in Central Florida. The first approach used a Poisson regression model that predicted the number of WWD crashes in a roadway segment based on WWD citations, 911 calls, traffic volumes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…This is no surprise, as the higher AADT means more potential WW drivers. Sandt et al also found that the higher AADT value increases the risk of WWD crashes when predicting WWD crash risk on different road segments in Central Florida ( 15 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is no surprise, as the higher AADT means more potential WW drivers. Sandt et al also found that the higher AADT value increases the risk of WWD crashes when predicting WWD crash risk on different road segments in Central Florida ( 15 ).…”
Section: Resultsmentioning
confidence: 98%
“…Their findings show that the WWD events increase when left-turn volume toward entrance ramp increases and stopping vehicles at exit ramp decreases. Sandt et al identified WWD hotspots by modeling crash risk and analyzing traffic management response times ( 15 ). They developed a Poisson regression model to predict WWD crashes at different roadway segments in the Central Florida area based on WWD event data (e.g., crashes, citations, and 911 calls with GPS location) and roadway data (e.g., interchange locations, interchange types, and traffic volumes).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper will estimate these future savings because of LED and RFB countermeasures for the FTE system. Previous efforts by the authors show the ability of the developed WWCR modeling and optimization approach to accurately identify limited access segments with high WWCR and predict WWCR reductions for individual exits (7,(21)(22)(23)(24)(25). By incorporating injury costs for WWD crashes, this approach can be used to determine the life-cycle benefits of advanced WWD countermeasure deployments, calculate B/C ratios for individual exits, and compare RFB and LED countermeasures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research included a benefit-cost analysis of these LED WWD countermeasures resulting in a benefit-cost ratio of 13.1, however details of this analysis were not found (12). UCF researchers have built models to predict WWD crashes and non-crash events using various roadway characteristics and driver demographics, developed an optimization approach to help agencies effectively deploy WWD countermeasures, surveyed drivers and law enforcement officers about WWD behavior, analyzed the factors that affect law enforcement response time to WWD events, and evaluated LED and RFB WWD countermeasures installed on toll roads in South and Central Florida (1,(5)(6)(7)(13)(14)(15)(16)(17)(18)(19)(20)(21). However, none of this previous research involved benefit-cost analyses of ITS WWD countermeasures.…”
Section: Literature Reviewmentioning
confidence: 99%